Everyday Talk on Twitter: Informal Deliberation About (Ir-)responsible Business Conduct in Social Media Arenas. Issue 6 (July 2023) - Lundgaard, Daniel; Etter, Michael
Recent research has damped initial promises for democratic deliberation in social media arenas. Empirical studies find only low degrees of direct reciprocal interaction among participants, a lack of consensus orientation, and accelerated forms of communication that fail to meet traditional ideals of deliberation. In line with recent literature, we argue that traditional deliberative ideals are too narrow to embrace the potential contribution of social media for deliberation about (ir-)responsible business conduct. Instead, we propose to conceptualize social media as arenas for everyday talk, that is, everyday communication practices through which participants informally discuss and express opinions about current issues, thereby contributing to a broader deliberative system. In adopting this lens, we ask: How can everyday talk in social media contribute to deliberation about (ir-)responsible business conduct? Drawing on the latest insights from online deliberation studies, we develop a framework for evaluating everyday talk and propose that its deliberative quality depends on social media appropriate forms of justification, interactivity, equality, and civility. We apply this framework with an analysis of 260, 224 tweets about the role of business in climate change. Based on our findings, we critically discuss how everyday talk in social media can contribute to deliberation at the intersection of business and society.